INTEGRASI BUDAYA PRESTASI PADA FUNGSI PERENCANAAN PEMBINAAN MUTU DOSEN - Wahyudin Noor; Juhji Juhji (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This paper aims to explain the implementation of the planning function of lecturer quality development at UIN Imam Bonjol Padang, West Sumatera and integrating the cultural values of achievement in the planning function. This research uses a qualitative approach. Data collection techniques are done through interviews, observation, and documentation. Data analysis procedures use data reduction, data display, and verification. While the research subjects are leaders, lecturers, and students. The results of this study indicate that: a) The planning of lecturer quality development activities at UIN Imam Bonjol Padang, has been quite good. Nevertheless, the relatively minimal budgeting problems can affect the optimization of the realization of planned activities; b) Integrating the achievement cultural in the planning function of lecturer quality development activities in tertiary institutions, is to be an endeavor to initiate changes in tertiary institutions that constantly necessitates improved management in an increasingly efficient, effective and productive direction.